Multimoda hyperspectroscopy screening in women at risk of cervical cancer: results of a pilot study in a developing country (2017)
Background: Screening and treatment of pre-cancerous lesions is important for prevention of cervical cancer. Currently, most available screening tests for cervical cancer are limited by low sensitivity, prohibitive costs, logistics and technical concerns. This study evaluates the role of multimodal hyperspectroscopy (MHS) as a cost-effective, sensitive and user-friendly point-of-care machine for early detection in women at risk of pre-cancer lesions. Materials and Methods: Multimodal hyperspectroscopy of the cervix using the LuViva® Advanced Cervical Scan was performed first in a 1-minute procedure among 100 previously screened for cervical cancer using either visual inspection after application of acetic acid (VIA) or cytology within the last 120 days. This was then followed by obtaining human papilloma virus (HPV) samples and biopsies from women for histology. Results: Of the 22 women with abnormal Pap tests of at least low‑grade squamous intraepithelial lesion, 3 had CIN2+, 6 had CIN1, 4 were free of dysplasia at histopathology while 9 had cervicitis. All 3 of the CIN2+ recorded high likelihood of CIN2+ by MHS. However, HPV was negative for all 3 women. The machine classified 1 of 1 CIN1s and 7 of the 13 women without dysplasia or cervicitis as low or moderate risk for CIN2+ (40% specificity); of the 37 women who were VIA+, 81% were classified as high risk, and 66% of 37 women with normal Pap tests and biopsy were either at moderate or low risk. Conclusions: The findings from this pilot study show that MHS reduced the percentage of unnecessary colposcopy and biopsy by 37.5%. It was also able to differentiate between VIA+ and Pap negative women suggesting its potential of being a point-of-care primary and objective screening test.